I love you every day! - Kosara, Tori 1985- (New York, NY DK Publishing, 2020)
"Tell your little one you love them no matter how they're feeling!"--
English Stories
On board pages
Keywords: Board books; Emotions -- Juvenile fiction; LEGO toys -- Juvenile fiction; Love -- Juvenile fiction; Picture books for children; Stories in rhyme; Board books; Emotions; LEGO toys; Love; Juvenile works; Picture books